GSK-3β coordinates axonal microtubule organization through Shot and Tau - André Voelzmann; Lubna Nuhu-Soso; Alex E. Roof; Sanjai Patel; Hayley Bennett; Antony Adamson; Gareth J. O. Evans; Marvin Bentley; Ines Hahn (Proceedings of the National Academy of Sciences, 2026)
Glycogen Synthase Kinase 3β (GSK-3β) is a key coordinator of neuronal development and maintenance; hyperactive GSK-3β is linked to neurodevelopmental and -degenerative diseases and therefore a promising therapeutic target. In neurons, GSK-3β coordinates the cytoskeleton by phosphorylating microtubule-binding proteins. In this study, we found that tight regulation of GSK-3β kinase activity is required for the maintenance of parallel microtubule bundles in Drosophila and rat axons. Up- or downregulation of GSK-3β led to axons forming pathological swellings in which microtubule bundles disintegrated into disorganized, curled microtubules. We identified the microtubule bundling proteins Shot and Tau as key GSK-3β targets and found that GSK-3β exerted its regulatory effect on microtubule bundling through them. GSK-3β regulates the ability of Shot and Tau to attach to microtubules and/or Eb1. Misregulation of GSK-3β leads to the loss of Eb1–Shot-mediated guidance of polymerizing microtubules into parallel bundles, thus causing disorganization. We propose that microtubule disorganization during both active and inactive states of GSK-3β links its hyperactivity to neurodegeneration and may explain why global GSK-3β inhibition has failed in clinical trials.